Integrated Metaheuristic Differential Evolution Optimization Algorithm and Pseudo Static Analysis of Concrete Gravity Dam - Taher Memarian; Yaser Shahbazi (Civil Engineering Journal, 2017)
A differential evolution-algorithm-based optimum design method is presented for concrete gravity dams under stability, principal stress, and sliding constraints. A gravity dam is a large scale hydraulic structure providing its stability based on weight of concrete volume. Hence, optimization of dam cross-section leads to an economic and low cost structure. For this aim, a general dam section is reconstructed with seven proper horizontal and vertical geometric parameters which take into account all possible cross section shapes. Weight of dam is considered as goal function and the optimization problem of geometric parameters is solved using DE algorithm. The DE algorithm written as a MATLAB code are applied to Four benchmark gravity dams including Middle Fork, Richard, Pine Flat, and Friant. The comparison of DE optimum solutions with real dimension of dams and another optimization method in literature shows the performance of the DE algorithm. In mentioned benchmark dams, there are 26.82%, 30.11%, 25.31%, and 20.93% of weight reduction Compared to real values, respectively. Also, optimization results of DE algorithm are compared with literatures. The comparison shows 3.55%, 5.1%, 19.13% and 12.14% reduction of weight compared to GA and PSOD algorithms, respectively.